New distribution records of Epiophlebia laidlawi Tillyard, 1921 (Insecta: Odonata) in Bhutan - Tshering Dorji (Journal of Threatened Taxa, 2015)
An opportunistic survey for Epiophlebia laidlawi larvae was carried out within five districts in Western and Central Bhutan from 2012 to 2014.  The study recorded a total of 21 individuals from five districts and also recorded F0, F3 and F8 instars larvae for the first time in Bhutan.  The study adds December and February as possible months to record F0 instars within its range.  The record of E. laidlawi from Bumthang District extends its range to the eastern most part of the Himalayas, and it also extends its range from Chhukha District to its southern most range within Bhutan.  A record from Punakha District fills the gap between the previous and current record of E. laidlawi from Wangchhu basin in Western Bhutan and Drangmechhu basin spanning central and eastern Bhutan with Punatshangchhu basin in between.  The record from Trongsa District emphasises the importance of the study area as E. laidlawi’s habitat.  The extent range of E. laidlawi within Bhutan is now extended to six districts, viz., Haa, Thimphu, Chhukha, Punakha, Trongsa and Bumthang.